AB0750 Long-term efficacy and safety of anti TNF-α therapy in 4 patients with refractory takayasu's arteritis. (23rd January 2014) - Schiavon, F.; Carraro, V.; Riato, L.; Favero, M.; Punzi, L.
Abstract : Background: Takayasu arteritis (TA) is a chronic large vessel vasculitis of an unknown cause, affecting the aorta and its primary branches, that leads to wall thickening, stenosis and thrombus or anuerysm formation. Therapy consists of the administration of glucocorticoids (CS) but relapse or steroid dependence may lead to associate immunosuppressive agents to achieve remission and prevent new arterial lesions. The pathogenesis of TA includes vessel injury mediated by T cells, NK cells, γ/δ cells and macrophages that secrete pro inflammatory cytokines including TNF-α. Therefore TNF-α antagonist might be useful in TA therapy. Only few cases of the use of anti TNF-α agents in TA patients are reported to date. We report the medium and long-term efficacy and tolerance of TNF-antagonist Infliximab in 4 patients affected by TA refractory to conventional therapies Methods: We evaluated 4 patients treated with anti TNF therapy (Infliximab) with a follow-up of 44.25±27.1 months (range from 7 to 72 months).The patients (all females) fulfilled the diagnosis of TA according to the ACR 1990 criteria. Their mean age was 23±3.3 years and mean disease duration was 67.75±78.03 months. All patients underwent detailed clinical examination and laboratory evaluation including complete blood count, ESR, CRP, chest radiograph, ECG, peripheral vascular Doppler and PET-CT. Disease activity was considered by clinical, biological and PET-CT features. All the patients were initially treated with high doses of CS (prednisone 1mg/kg/daily) and immunosuppressive drugs in order to gain a better control of the vasculitis and to rapidly reduce steroid administration. After 3 months patients presented poor respons to clinical and biological features and were dependent on high doses of steroid. Therefore we started with Infliximab 3 mg/kg. The dose was increased to 5mg/kg in all patients due to the temporary efficacy of 3 mg/kg. Results: After 4 weeks all patients felt better and they did not complain of fever, carotodynia, tiredness or thoracic pain. Laboratory tests showed a rapidly decrease of CRP from 74.2±21.61 mg/l to 2.25±0.5 mg/l and an improvement of anaemia. After 1 year we were able to reduce steroids to 5 mg/daily and immunosuppressive drugs without disease relapse in three patients and tapered prednisone to 10 mg daily in the fourth. A new PET-CT was performed on all patients after 1 year of therapy with Infliximab and we observed the disappearance of arterial hypermetabolism in three patients. They continue to be treated with Infliximab every 8 weeks without clinical, biological and radiological evidence of recurrence of the disease Conclusions: Infliximab demonstrated to be effective in TA in all the parameters reflecting disease activity. Nevertheless, we were forced to administer the dose of 5 mg/kg due to the temporary efficacy of 3 mg/kg. Three of our patients achieved clinical, radiological and biological remission, the fourth tapered the dose of CS and immunosuppressive drug. Using-2-deoxiglucose uptake, arterial hypermetabolism on PET scan disappeared in the remission patients. In all 4 patients, biological markers normalized. During follow-up, no side effects or reaction to the infusion were observed. Our data confirm efficacy and safety of Infliximab in TA therapy Disclosure of Interest: None Declared